Intraventricular haemorrhage in premature babies at Dr George Mukhari Hospital, Pretoria - Lentsoane, Tiisotso Lenake (University of Limpopo (Medunsa Campus), 2011)
Background: Intraventricular hemorrhage (IVH) is a known complication occurring in the first week of life in premature neonates. The exact time of its occurrence and the ideal time to perform diagnostic imaging investigation remain controversial. Objectives: 1. To determine the incidence of intraventicular hemorrhage in premature babies at Dr George Mukhari Hospital, Pretoria. 2. To determine the timing at which bleeding occurs. 3. To determine if the rate of diagnosing intraventicular hemorrhage improves when performing ultrasound via the posterior fontanelle. 4. To determine the risk factors for intraventricular haemorrhage Materials and methods: The study included 60 premature babies of gestational age of less than 32 weeks that were admitted to our neonatal Intensive Care Unit over a two months period and screened for IVH. They were grouped into three categories according to their weight at birth, and according to their gestational age. All babies had a cranial ultrasound on day 1, 3 and 7. Results: We found that the overall incidence of IVH among premature babies was 28%. Although it did not reach statistical significance, the incidence was found to be inversely related to the birth weight and gestational age. The majority of the bleeds occurred within the first day of life and were mostly grade I and II according to Papile’s classification. The use of inotropes was found to be significantly associated with development of IVH. We also found that scanning through the posterior fontanelle did not significantly increase the rate of diagnosis for IVH.
Thesis MSc.(Med)(Virology)-- University of Limpopo, 2011
Keywords: Haemorrhage; Premature babies